Instrument redesign for evaluating nursing organizational climate at hospital service - Annia Lourdes Iglesias Armenteros; Julia Maricela Torres Esperón (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2019)
Foundation: organizational climate has been studied since the XX century and its first research started in the corporate area. These results transcended to other fields as the health sector where contextualization has been developed according to its ethical characteristics. Objectives: to redesign an instrument for evaluating nursing organizational climate in hospitals. Methods: development research realized at the University Pediatric Hospital Paquito González Cueto Cienfuegos from January to May 2017 for which a documentary review was done about the instruments: questionnaires of Litwin y Stringer, questionnaires of organizational diagnosis, Model of Meyer and Allen, Wes questionnaire, organizational climate inventory, descriptive questionnaire of organizational climate of Halpin y Crofts, organizational health inventory of Hoy y Feldmany. For the coherence of the characteristics of the health sector and the experiences with the application of this instrument in it, it was decided to take The inventory of Organizational Climate adapted by Vivian Noriega. Once designed the instrument it was submitted to expert valuation. Results: most experts assessed the relation between the instrument and the objectives for its design as favorable, and comprehensible the different items and their contextualization. Conclusion: the proposal presented may constitute a mechanism for periodical measurement and be part of the structural capital of hospital institutions. Its application may improve the assistance to patients on the basis of a favorable organizational climate.